(untitled) (Journal of Atomic and Molecular Sciences, 2018)
We review the methods to preserve the initial state populations in a fast harmonic trap expansion. The design of the time dependence of the frequency using inverse techniques presents advantages over the slow adiabatic approach, band-bang methods, or the non-local "transitionless tracking'' algorithm. Many operations with cold atoms make use of adiabatic expansions and would benefit from such a shortcut to adiabaticity.